Efficacy of physical activities to develop Social Communication Skills in Children with Autism - Alzoubi, Ibrhim Hassan (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
Abstract There are a number of strategies related to physical activities that can be used to keep the child with autism spectrum disorder manage their symptoms. 20 minutes of exercise is highly recommended, depending on the age and health of the autism spectrum disorder children as well as other family members engaging in the activity (parents and siblings). When choosing which exercises to conduct, take into account the perspectives of the kid with autism spectrum disorder as well as what kind of activities they love most. The research has been carried out in Abu Dhabi with aim to get clear understanding of how physical activity regulates behavioral patterns. Moreover the success rate of physical activity in managing social incoherence among children with autism will be evaluated. Along with the effectiveness of parental and educator assistance in facilitating social contact among children diagnosed with autism spectrum disorder to determine whether physical activity is useful for all children diagnosed with autism spectrum disorder. The research will suggest by including reference from previous researches and meta-analysis that Physical activities and yoga decreases blood pressure, enhance insulin sensitivity and sleep quality, and lower the risk of some chronic diseases. Exercise triggers the release of endorphins and monoamine neurotransmitters that act as a brain-mimicking substitute for antidepressants, making physical activity an effective strategy for autism spectrum disorder children (Howells et al., 2019). Many global institutions employ exercise as a strategy for managing autistic children, but its efficacy remains a topic of controversy, especially when it comes to using games and physical activity for autism treatment. The study will tend to find out the efficacy of exercise on autistic children behavioral patterns. The research will use quantitative analysis by using SPSS to evaluate weather physical activity is good strategy to enhance social communication among children of 10-14 age in particular. Two types of questionnaire would be composed and later analyzed in this research one to check child’s caliber to understand concept of social gatherings in school or home and one for parents or teacher to respond by evaluating child performance in tests. It has been found out that Autistic behavior can be treated with increased physical activities including games as per the results extracted by SPSS.